The microbiology of ostrich meat with reference to prevalent microbial growth and bruises in carcasses - Schnetler, Demona Charlotte (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc Food Sc (Food Science))--University of Stellenbosch, 2009.